Non-restorative Sleep Caused by Autonomic and Electroencephalography Parameter Dysfunction Leads to Subjective Fatigue at Wake Time in Shift Workers - Gorlova, Sofya; Ichiba, Tomohisa; Nishimaru, Hiroshi; Takamura, Yusaku; Matsumoto, Jumpei; Hori, Etsuro; Nagashima, Yoshinao; Tatsuse, Tsuyoshi; Ono, Taketoshi; Nishijo, Hisao (Frontiers in Neurology, 2019)
Sleep is a physiological state that plays important role in the recovery of fatigue. However, the relationship between the physiological status of sleep and subjective fatigue remains unknown. In the present study, we hypothesized that the non-recovery of fatigue at wake time due to non-restorative sleep might be ascribed to changes in specific parameters of electroencephalography (EEG) and heart rate variability (HRV) in poor sleepers. Twenty healthy female shift-working nurses participated in the study. Subjective fatigue was assessed using the visual analog scale (VAS) at bedtime and wake time. During sleep on the night between two consecutive day shifts, the EEG powers at the frontal pole, HRV based on electrocardiograms, and distal-proximal gradient of skin temperature were recorded and analyzed. The results indicated that the subjects with high fatigue on the VAS at wake time exhibited 1) a decrease in deep non-rapid eye movement (NREM) (stageN3) sleep duration in the first sleep cycle; 2) a decrease in REM latency; 3) a decrease in ultra-slow and delta EEG powers, particularly from 30 to 65 min after sleep onset; 4) a decrease in the total power of HRV, particularly from 0 to 30 min after sleep onset; 5) an increase in the very low frequency component of HRV; and 6) a smaller increase in the distal-proximal gradient of skin temperature, than those of the subjects with low fatigue levels. The correlational and structural equation modeling analyses of these parameters suggested that an initial decrease in the total power of HRV from 0 to 30 min after sleep onset might inhibit the recovery from fatigue during sleep (i.e., increase the VAS score at wake time) via its effects on the ultra-slow and delta powers from 30 to 65 min after sleep onset, stageN3 duration in the first sleep cycle, REM latency, and distal-proximal gradient of skin temperature. These findings suggest an important role of these physiological factors in recovery from fatigue during sleep, and that interventions to modify these physiological factors might ameliorate fatigue at wake time.